Optimizing bioethanol from sago dregs for Honai burner stoves: A case study in Papua - Numberi, Johni Jonatan; Uniplaita, Tiper Korneles Muwarberto; Suwandi, Agri; Siregar, Januar Parlaungan; Ekayuliana, Arifia; Joni, Joni; Palamba, Pither; Liga, Marthen (National Research and Innovation Agency, 2025)
Indonesia harbors considerable prospects for bioethanol fuel generation. Underscoring the imperative for establishing optimal fuel concentrations and appropriate burners to facilitate sustainable energy alternatives; this study endeavored to identify the optimal bioethanol concentration sourced from sago waste for application in Honai burners, evaluating the resultant flame output for domestic energy in Papuan custom houses. This analysis adopted an integration of pre-experimental frameworks along with experimental ones. In the early trial stage, concentrations of bioethanol were thoroughly examined concerning low heat value (LHV), specific gravity, viscosity, gas chromatography, and Fourier transform infrared (FTIR) analysis to identify the best fuel characteristics. Following this, the experimental phase assessed flame characteristics, encompassing temperature, fuel mass flow rate, and emissions from combustion gases within the Honai burner. Pre-experimental findings suggest that an 80 % bioethanol concentration is ideal for the Honai burner, displaying a viscosity of 1.03 cP, a density of 0.82 g·L⁻¹, a gas chromatography content of 61.04 %, an LHV of 16.166 MJ/kg, and a heat release rate of 140 kW·m⁻². The experimental phase indicates that a 14-hole burner oriented at a 45° angle yields optimal performance, achieving stable flame temperatures between 480 °C and 750 °C with a fuel flow rate of 60 mL·min⁻¹. Analysis of combustion gases indicates minimal emissions, with carbon monoxide (CO) registering at 0.01 %, carbon dioxide (CO₂) at 0.2 %, and hydrocarbons (HC) at 27 ppm. In summary, this study offers a feasible approach to addressing energy challenges, meeting demand, enhancing accessibility, ensuring availability, and promoting regional energy autonomy for Papuan households in remote locales through the utilization of bioethanol derived from sago dregs in Honai burner cooking devices.